Review of Advertising Ethics in Creative Content: Analysis of Head & Shoulders Advertising Violations Joe Taslim In the Morning Fresh, Active, Dandruff Wet Again - Hagi, Dhiyyaul; Revaya, Muhammad (Educationist: Journal of Educational and Cultural Studies, 2023)
The rapid development of digital advertising in Indonesia brings its own advantages for advertisers from telecommunications companies. Along with increasing internet penetration, advertisers are increasingly shifting their marketing efforts to online platforms. Many companies from various fields advertise as creatively as possible to attract the attention of the audience so that the audience buys or uses the advertised product. Head & Shoulders is one of the shampoo brands engaged in medicine and household health. Head & Shoulders also has creative ideas in advertising the brand to attract audiences to buy the product. So that in January 2021, Head & Shoulders chose Joe Taslim as the Brand Ambassador for the Head & Shoulders advertisement. But in the end the advertisement had to be stopped because it was considered to have violated the broadcasting code of ethics in Indonesia. But apart from the code of advertising ethics, there are also advertising ethics that must be considered for every brand that wants to advertise the product. In this study, the researcher discusses the violations contained in the Head & Shoulders advertisement. The purpose of this research is to deepen the knowledge of advertising ethics because in advertising ethics there is a lot to pay attention to. The method used by the researcher is a qualitative method using content analysis and for the validity of the observed data, the researcher looks for references that support this research.